2018
DOI: 10.3390/w10111633
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variations in Water Uptake Patterns of Winter Wheat under Different Irrigation and Fertilization Treatments

Abstract: Irrigation and fertilization both affect the water cycle in agricultural ecosystems. It is difficult to quantify root water uptake (RWU) which varies with crop development and seasons. In this study, a Bayesian mixing model (MixSIAR) coupling with dual stable isotopes (D and 18 O) was used to quantify RWU patterns for winter wheat under different irrigation and fertilization treatments between 2014 and 2015 in Beijing, China. The main RWU depth during the greening-jointing, jointing-heading, heading-filling, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…In the study by Ma and Song (2016) maize was fertilized with different nitrogen application rates from zero to 368 kg N ha −1 , resulting in clear differences in the proportional contribution of soil water at different depths. Similarly, fertilization with 105 kg N ha -1 or irrigation of 20 mm during the greening-jointing stage significantly promoted soil water uptake of winter wheat at 70-150 cm and 150-200 cm whereas other treatments led to the much shallower RWU depths of 0-20 cm (Ma and Song, 2018).…”
Section: Rwu Under Different Irrigation and Fertilization Conditionsmentioning
confidence: 94%
See 2 more Smart Citations
“…In the study by Ma and Song (2016) maize was fertilized with different nitrogen application rates from zero to 368 kg N ha −1 , resulting in clear differences in the proportional contribution of soil water at different depths. Similarly, fertilization with 105 kg N ha -1 or irrigation of 20 mm during the greening-jointing stage significantly promoted soil water uptake of winter wheat at 70-150 cm and 150-200 cm whereas other treatments led to the much shallower RWU depths of 0-20 cm (Ma and Song, 2018).…”
Section: Rwu Under Different Irrigation and Fertilization Conditionsmentioning
confidence: 94%
“…Variability in RWU patterns as a function of the growing stage has also been reported for other crops, both herbaceous and trees. For instance, the primary soil depths of RWU for winter wheat (Triticum aestivum) were found to be between 0 and 50 cm for the majority of the growing period (Zhang et al, 2011a;Wang et al, 2016;Yang et al, 2018), and especially in the 0-20 cm soil layers during the wintering and seedling phases (Zhao et al, 2018a), and increasing depths were observed during the end of the growing period (Cheng and Liu, 2017;Ma and Song, 2018) and up to 220 cm in the filling stage (Guo et al, 2016). Similar trends were found for cotton (Li et al, 2017).…”
Section: Water Sources For Plant Water Uptakementioning
confidence: 99%
See 1 more Smart Citation
“…Root water uptake patterns are often discussed for their important role in plant water relations, but responses of crop root water uptake patterns to drought took place in pots or under controlled conditions (e.g., Zegada-Lizarazu & Iijima, 2004;Araki & Iijima, 2005), so that information on field conditions is particularly scarce, except maize (Ma & Song, 2016), wheat (Ma & Song, 2018), oilseed rape, and barley in monoculture (Wu et al, 2016). Furthermore, studies comparing the role of different cropping systems for crop water uptake are completely lacking.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this may be due to the increment of water content and heat capacity of the root layer soil caused by freezing irrigation. This prevented drastic changes in temperature in the alfalfa root zone before winter and provided good environmental conditions to acclimatize alfalfa to cold conditions, thus improving the alfalfa overwintering rate [70][71][72][73][74]. Also, repeated thawing and freezing of soil and the days and nights after freezing irrigation played a role in loosening the soil and improving alfalfa habitat conditions.…”
Section: Estimating the Source Contribution To Xylem Water After Freementioning
confidence: 99%